The Analysis Of Online Learning Tools Based On Students Survey Due To Covid-19 Pandemic - Siti Fitria Yonalia; Putu Harry Gunawan (eProceedings of Engineering, 2021)
Abstract The Covid-19 pandemic situation that occurred in 2021 has made changes to a fast pattern in various sectors, one of which is education. There are various methods used to secure teaching and learning activities by minimizing physical contact in order to reduce the increase in the viral transmission curve. Changing the method from offline to online at a rapid pace raises a new problem that reduces the effectiveness of learning activities for students. Some of these things are caused by the quality of the internet network that is not optimal, constraints in the habituation of using online learning methods and differences in understanding of the material through the use of the video conference application. This study will provide a comprehensive explanation of the level of effectiveness of online learning in the long and short term with nonparametric statistical analysis on categorical data analysis through the Chi-Square test with a research sample of 150 students spread across the University of Jakarta and Bandung. Keywords: Covid-19, Effectivity, Online Learning, Video Conference Application.